Evaluation of a Standardized Protocol for Plasma Rich in Growth Factors Obtention in Cats: A Prospective Study - Miguel-Pastor, Laura; Satué, Katy; Chicharro, Deborah; Torres-Torrillas, Marta; del Romero, Ayla; Peláez, Pau; Carrillo, José M.; Cuervo, Belén; Sopena, Joaquín J.; Cerón, José J.; Rubio, Mónica (Frontiers in Veterinary Science, 2022)
Introduction Platelet-rich plasma (PRP) is an autologous plasma with platelet (PLT) concentration above that of whole blood (WB). PLTs contain growth factors (GFs) that promote tissular repair. Objectives To determine and compare the concentrations of PLT, red blood cells (RBC) and white blood cells (WBC) between WB samples, PRP and platelet poor plasma (PPP) samples; and to analyze the concentrations of platelet-derived growth factor BB (PDGF-BB) and transforming growth factor β1 (TGF-β1) in the PRP and PPP of healthy adult cats using a standardized protocol with PRGF®-Endoret® characteristics. Material and Methods WB was collected from 30 cats. PRP was obtained following three centrifugation protocols using PRGF®-Endoret® technology: 255, 260, and 265 g for 10 min each. The cellular components, RBC, WBC, PLT, and the concentrations of PDGF-BB and TGF-β1 in the PRP and PPP fractions were determined for each protocol. Results PLTs in the PRP fraction were statistically higher than WB, with no statistical differences between PPP and WB. In PRP fraction, PLT concentration was increased 1.4 times on average at 255 g; 1.3 times at 260 g and, 1.5 times at 265 g without statistical differences among them. The mean platelet volume (MPV) was significantly higher in WB compared to PRP and PPP fractions without significant differences between protocols. Compared to WB, the number of RBCs and WBCs was reduced by 99% and by more than 95% in PRP and PPP respectively, without significant differences between protocols. PDGF-BB concentrations were statistically higher in PRP than in PPP fractions, however, TGF-ß1 concentrations did not vary between fractions at 260 g. Comparing the three protocols within PRP and PPP fractions, no differences in PDGF-BB and TGF-ß1 concentrations were observed. Clinical Relevance The study shows scientific evidence regarding the obtention of PRP in cats using the PRGF®-Endoret® technology for the quantification of PDGF-BB and TGF-ß1. At 265 g for 10 min, PLT concentration was increased 1.5 times with unnoticeable erythrocytes and leukocytes in the samples. These results clearly show that the PRGF®-Endoret® methodology is suitable to obtain PRP in cats. Further studies are needed to determine the clinical efficacy of the obtained PGRF in the treatment of different pathologies in cats.